On implicit metafiction - Baetens, Jan (Cadernos de Literatura Comparada, 2024)
A more rewarding outcome of our interest in metafiction would be to supersede the vague and somewhat bloodless statement that when reading fiction we should not forget the fact that we are reading fiction. It should deliver a more precise and inspiring lesson, not on the fact that we are reading fiction, but on the way in which this fiction has been made and how readers can process it. For this reason, metafictionality should be considered a subfield of the larger domain of metatextuality, that is those elements and mechanisms of the text that hint at the structures and properties of the text itself.